Approach at the emergency surgery at obturation ileus in colorectal cancer patient - F. Sh. Akhmetzyanov; N. A. Valiyev; V. I. Egorov; B. Sh. Bikbov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study early outcomes of surgical treatment of intestinal obstruction of neoplastic origin. Material and methods. Overall 730 patients operated for acute bowel obstruction of neoplastic origin for the interims of 1993-2005 and 2010-2016 were studied. All operations were carried out urgently for decompensated intestinal obstruction within 1 day after admission to medical institution. Urgent operations were performed according to oncologic treatment principles in the same way as elective surgery. Results. In 603 of 730 patients (82.6%) the tumor was localized distally to the transverse colon. Early postoperative motility for the period of 1993-2002 was 22.8%, for the period of 2011-2016 - 10.2%. The rate of primary radical interventions in the general framework of operations was 88.3%. Conclusions. Original approach to colorectal cancer surgical treatment complicated by acute large-intestinal obstruction resulted in significant decrease in early post-operative motility. Successful performance of radical operations at the first treatment stage considerably facilitates further treatment, social and medical rehabilitation.